The association between alcohol outlet density and alcohol use among urban and regional Australian adolescents. (9th October 2015) - Azar, Denise; White, Victoria; Coomber, Kerri; Faulkner, Agatha; Livingston, Michael; Chikritzhs, Tanya; Room, Robin; Wakefield, Melanie
Abstract: Aims: While recent evidence suggests that higher alcohol outlet density is associated with greater alcohol use among adolescents, influence of the four main outlet types on youth drinking within urban and regional communities is unknown. This study provides the first investigation of this relationship. Design: Repeated cross‐sectional surveys with random samples of secondary students clustered by school. Mixed‐effects logistic regression analyses examined the association between each outlet type and the drinking outcomes, with interaction terms used to test urban/regional differences. Setting: Australia, 2002–11. Participants: Respondents participating in a triennial survey (aged 12–17 years); 44 897 from urban settings, 23 311 from regional settings. Measurements: The key outcome measures were past month alcohol use, risky drinking among all students and risky drinking among past week drinkers. For each survey year, students were assigned a postcode‐level outlet density (number of licences per 1000 population) for each outlet type (general, on‐premise, off‐premise, clubs). Findings: Interaction terms revealed a significant association between off‐premises outlet density and risky drinking among all adolescents in urban (odds ratio = 1.36, 95% confidence interval CI = 1.05–1.75, P < 0.05) but not regional areas. Similarly, club density was associated with the drinking outcomes in urban communities only. General and on‐premises density was associated with alcohol use and risky drinking among all adolescents. Conclusions: Higher densities of general, on‐ and off‐premises outlets in an adolescent's immediate neighbourhood are related to increased likelihood of alcohol consumption among all adolescents. The density of licensed clubs is associated more strongly with drinking for urban than for regional adolescents.